Distinct early-life mechanisms of quantity discrimination in domestic chicks - Maria Loconsole; Elisa Tedaldi; Lucia Regolin (PLoS ONE, 2026)
In research on animal numerical cognition, newly hatched domestic chicks have been shown to rely on distinct strategies when confronted with quantitative choices. In some conditions, such as after imprinting on a specific set of objects, chicks preferentially approach the larger set of familiar items, indicating sensitivity to magnitude. In other conditions, however, their responses are governed not by magnitude per se, but by the degree of similarity between the test objects and a previously experienced set, where similarity is defined in terms of conformity to specific perceptual constraints, such as the possibility of a symmetrical division into identical subsets (as in composite versus prime sets of items). In the present study, we sought to replicate both phenomena while aligning key methodological features, including the test arena, the comparison (5 vs. 9), and the age at testing. One group of chicks was imprinted on a set of identical objects to test preference for larger familiar set; another group was habituated to even-numbered sets to assess sensitivity to perceptual asymmetry in prime-numbered ones. We successfully replicated both effects: chicks preferred the larger set after imprinting and showed longer inspection of the prime-numbered set after habituation, despite its smaller magnitude. Our results show that different mechanisms supporting quantity discrimination are available from the earliest stages of life and can be triggered by task- or environment-specific factors.